A supported metallocene catalyst and its preparation method and application

By using inorganic support-magnesium halide composite support and polyethylene polycarboxylic acid ester, the supported metallocene catalysts are solved in the poor form and sticky problems in polyethylene production, achieving efficient catalytic and cost-saving effects.

CN119751719APending Publication Date: 2025-04-04SHANGHAI RES INST OF CHEM IND CO LTD +2
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202510012007.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-03
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

In the industrial production of polyethylene, existing supported metallocene catalysts have problems such as poor particle morphology, difficulty in controlling and serious sticking kettle, which affects their application effect.

Method used

The inorganic support-magnesium halide composite support is used, and the particle morphology of the catalyst and the loading effect of the active components are improved by activating the support and introducing polyethylene polycarboxylic acid ester as a regulator.

Benefits of technology

The catalytic ethylene polymerization activity is improved, the amount of alkyl aluminoxane is reduced, the production cost is saved, and the morphology control and industrial application effect of the catalyst is significantly improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005229117930000051
    Figure BDA0005229117930000051
  • Figure BDA0005229117930000201
    Figure BDA0005229117930000201
  • Figure BDA0005229117930000211
    Figure BDA0005229117930000211
Patent Text Reader

Abstract

The present invention relates to a supported metallocene catalyst and a preparation method and application thereof. The catalyst provided by the present invention has high catalytic ethylene polymerization activity and good copolymerization performance, and the catalyst provided by the present invention is used to catalyze ethylene polymerization to prepare a polymer non-stick kettle.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a supported metallocene catalyst and a preparation method and application thereof. Background Art

[0002] Metallocene catalytic system is a strong candidate in the field of polyolefins after Ziegler-Natta catalyst. Metallocene catalyst is an organic metal catalyst formed by cyclopentadienyl and its derivatives coordinated with transition metals. It forms a high-efficiency catalytic system with co-catalysts such as alkylaluminoxane. It is a current research hotspot and is currently replacing ZN-type catalysts. Its catalytic mechanism is that metallocene complexes and co-catalysts form cationic active catalytic centers. Metallocene complexes refer to organic metal complexes formed by transition metal elements (such as IVB group elements titanium, zirconium, hafnium) or rare earth elements coordinated with at least one cyclopentadiene and its derivatives. In addition to alkylaluminoxane, co-catalysts can also use organic boron compounds.

[0003] Metallocene catalysts have the advantages of high activity, uniform polymerization products, and good transparency, but the polymers obtained in the homogeneous system have problems such as poor particle morphology, difficulty in control, and serious sticking to the kettle, which greatly affects its industrial application. Therefore, supported metallocene catalysts came into being. Common carriers include inorganic carriers such as silica gel (SiO2), magnesium chloride, alumina, clay, molecular sieves, as well as polymer carriers and inorganic / organic composite carriers. With a carrier with better particle morphology, polyethylene will also have a better morphology during the formation process and a higher apparent density.

[0004] At present, the carrier used for metallocene catalyst loading is mainly SiO2, which can meet the needs of industrial production due to its suitable pore volume, pore size distribution, high specific surface area, good bulk density and mechanical strength. However, due to the small number of reactive groups on the surface of silica gel, the free water and hydroxyl groups on the surface are harmful to the catalyst ligands. Conventional loading methods, due to the small number of reactive groups on the surface of silica gel, the reaction capacity of MAO and silica gel is limited, the ability of silica gel to load MAO is limited, the ability to load metallocene is also small, and the catalytic activity of the carrier is not high.

[0005] Therefore, it is necessary to further improve the supported metallocene catalyst to make it more suitable for industrial production of polyethylene. Summary of the invention

[0006] The first aspect of the present invention provides a metallocene catalyst prepared by a method comprising the following steps:

[0007] 1) providing a magnesium halide alcoholate solution;

[0008] 2) adding the inorganic carrier to the magnesium halide alcoholate solution, impregnating, and obtaining an inorganic carrier-magnesium halide composite carrier;

[0009] 3) Activating an inorganic carrier-magnesium halide composite carrier;

[0010] 4) adding the activated inorganic carrier-magnesium halide composite carrier, polyethylene polycarboxylate, and co-catalyst to the solvent, mixing, and separating the solid product;

[0011] 5) adding the solid product separated in step 4) and the metallocene compound into the solvent, mixing them evenly to obtain a metallocene catalyst.

[0012] A second aspect of the present invention provides a method for preparing a metallocene catalyst, comprising:

[0013] 1) providing a magnesium halide alcoholate solution;

[0014] 2) adding the inorganic carrier to the magnesium halide alcoholate solution, impregnating, and obtaining an inorganic carrier-magnesium halide composite carrier;

[0015] 3) Activating an inorganic carrier-magnesium halide composite carrier;

[0016] 4) adding the activated inorganic carrier-magnesium halide composite carrier, polyethylene polycarboxylate, and co-catalyst to the solvent, mixing, and separating the solid product;

[0017] 5) adding the solid product separated in step 4) and the metallocene compound into the solvent, mixing them evenly to obtain a metallocene catalyst.

[0018] The third aspect of the present invention provides use of the metallocene catalyst described in the first aspect of the present invention in catalytic synthesis of polyethylene.

[0019] In certain embodiments, the magnesium halide alcoholate solution of the present invention is prepared by a method comprising the following steps:

[0020] 1-1) mixing a magnesium halide with an alcohol solution to obtain a mixture;

[0021] 1-2) Stirring the obtained mixture at a temperature of 50° C. or higher and lower than the boiling point of the alcohol solution.

[0022] In certain embodiments, the amount of the alcohol solution in step 1-1) is 0.5 to 30 mL of alcohol solution per gram of magnesium halide. In certain embodiments, the amount of the alcohol solution in step 1-1) is 2 to 10 mL of alcohol solution per gram of magnesium halide. In certain embodiments, the amount of the alcohol solution in step 1-1) is 3 to 8 mL of alcohol solution per gram of magnesium halide. In certain embodiments, the amount of the alcohol solution in step 1-1) is 5 mL of alcohol solution per gram of magnesium halide.

[0023] In certain embodiments, the time for stirring the obtained mixture in step 1-2) is 20 to 480 min, preferably 20 to 90 min, and more preferably 30 to 90 min.

[0024] In certain embodiments, the magnesium halide is selected from magnesium fluoride, chloride, bromide, or iodide.

[0025] In certain embodiments, the magnesium halide is selected from magnesium dihalide, C 1~8 Alkyl magnesium halide, C 1~8 Alkoxymagnesium halides and any combination thereof.

[0026] In certain embodiments, the magnesium halide is selected from magnesium dichloride, magnesium dibromide, methylmagnesium chloride, methylmagnesium bromide, methoxymagnesium chloride, methoxymagnesium bromide, ethoxymagnesium chloride, ethoxymagnesium bromide, butoxymagnesium chloride, butoxymagnesium bromide and any combination thereof. In certain embodiments, the magnesium halide is preferably magnesium dichloride.

[0027] In certain embodiments, the alcohol solution is an alcohol compound having 2 to 22 carbon atoms, preferably an alcohol compound having 2 to 11 carbon atoms, and more preferably an alcohol compound having 2 to 8 carbon atoms.

[0028] In certain embodiments, the alcohol solution is selected from ethanol, n-propanol, isopropanol, n-butanol, neobutanol, isooctyl alcohol, 2-ethylbutanol or ethylene glycol and any combination thereof. In certain embodiments, the alcohol solution is preferably ethanol.

[0029] In certain embodiments, the alcohol solution is ethanol, and in step 1-2), the resulting mixture is stirred at a temperature of 50° C. to 78° C. (preferably 65° C. to 78° C., such as 70° C.).

[0030] In certain embodiments, the amount of the inorganic carrier is 1 to 10 g of inorganic carrier per gram of magnesium halide. In certain embodiments, the amount of the inorganic carrier is 2 to 6 g of inorganic carrier per gram of magnesium halide. In certain embodiments, the amount of the inorganic carrier is 3 to 5 g of inorganic carrier per gram of magnesium halide. In certain embodiments, the amount of the inorganic carrier is 4 g of inorganic carrier per gram of magnesium halide.

[0031] In certain embodiments, the immersion temperature in step 2) is -80°C to 90°C. In certain embodiments, the immersion temperature in step 2) is -20°C to 80°C. In certain embodiments, the immersion temperature in step 2) is 60°C to 80°C. In certain embodiments, the immersion temperature in step 2) is 70°C.

[0032] In certain embodiments, the time of immersion in step 2) is 0.5 to 6 hours. In certain embodiments, the time of immersion in step 2) is 1 to 3 hours. In certain embodiments, the time of immersion in step 2) is 1.8 to 2.2 hours. In certain embodiments, the time of immersion in step 2) is 2 hours.

[0033] In some embodiments, the inorganic carrier is silica gel, physicochemically modified silica gel, molecular sieve or alumina, preferably silica gel or alumina. In some embodiments, the average particle size of the inorganic carrier is 50nm to 120μm, preferably 0.5 to 5μm. In some embodiments, the specific surface area of ​​the inorganic carrier is greater than or equal to 250m 2 In certain embodiments, the specific surface area of ​​the inorganic carrier is greater than or equal to 300 m 2 In certain embodiments, the specific surface area of ​​the inorganic carrier is 300 m 2 / g~600m 2 In certain embodiments, the specific surface area of ​​the inorganic carrier is 350 m 2 / g, 400m 2 / g, 450m 2 / g or 500m 2 / g.

[0034] In some embodiments, step 2) further comprises drying the inorganic carrier / magnesium halide composite carrier. In some embodiments, the preferred drying method is vacuum drying or temperature-controlled drying. In some embodiments, the drying method is temperature-controlled drying, the drying temperature is preferably 30°C to 300°C, more preferably 50°C to 150°C, and the drying time is preferably 10 to 600 min, more preferably 120 to 300 min, for example 240 min.

[0035] In certain embodiments, step 3) comprises:

[0036] 3-1) placing the inorganic carrier-magnesium halide composite carrier in a fluidized state;

[0037] 3-2) First raise the temperature to 200°C, then raise the temperature to 300°C to 800°C (preferably 400°C to 550°C, for example 400°C) and maintain a constant temperature.

[0038] In certain embodiments, in step 3-2), the temperature is maintained at a constant temperature for 60 to 360 min, preferably for 120 to 300 min, for example, 240 min.

[0039] In step 3-2), the temperature is first raised to 200°C to remove moisture in the carrier, and then raised to 300°C to 800°C to remove oxygen-containing substances on the surface of the carrier to prevent them from poisoning the catalytically active components.

[0040] In certain embodiments, the cocatalyst is an alkylaluminoxane (e.g., methylaluminoxane, ethylaluminoxane, isobutylaluminoxane, modified methylaluminoxane, polymethylaluminoxane), an alkylaluminum (e.g., trimethylaluminum, triethylaluminum, triisobutylaluminum, trihexylaluminum, butylaluminum) or an organic boron compound (e.g., tris(pentafluorophenyl)boron (B(C6F5)3), trityltetrakis(pentafluorophenyl)borate, dioctadecylmethyltertiaryaminetetrakis(pentafluorophenyl)borate).

[0041] In certain embodiments, the cocatalyst is selected from methylaluminoxane, ethylaluminoxane, isobutylaluminoxane, triethylaluminum, triisobutylaluminum. In certain embodiments, the cocatalyst is methylaluminoxane, triethylaluminum or triisobutylaluminum. In certain embodiments, the cocatalyst is methylaluminoxane.

[0042] In certain embodiments, the general formula of the polyethylene polycarboxylate is -[(CH2CH2)a-(CH2CHCOOR)b]n-, wherein n represents the molecular weight after polymerization, n is 1000-30000 g / mol, wherein the molar content of the carboxylate is 0.5-16%, and R is C 1~6 The alkyl group may be methyl, ethyl, n-propyl, isopropyl, n-butyl, sec-butyl, isobutyl, tert-butyl, n-pentyl or n-hexyl, preferably methyl, wherein a≥1, b≥1, and a and b are integers.

[0043] In certain embodiments, the polyvinyl polycarboxylate is a polyvinyl polycarboxylate having a methyl acrylate content of 5 to 7 mol % and a molecular weight of 3000 to 3200 g / mol.

[0044] In certain embodiments, the polyvinyl polycarboxylate is a polyvinyl polycarboxylate having a methyl acrylate content of 6 to 7 mol % and a molecular weight of 3000 to 3200 g / mol.

[0045] In certain embodiments, the amount of the polyvinyl polycarboxylate is 0.02g to 2g of polyvinyl polycarboxylate per gram of inorganic carrier-magnesium halide composite support. In certain embodiments, the amount of the polyvinyl polycarboxylate is 0.025g to 2g of polyvinyl polycarboxylate per gram of inorganic carrier-magnesium halide composite support. In certain embodiments, the amount of the polyvinyl polycarboxylate is 0.025g to 1.0g of polyvinyl polycarboxylate per gram of inorganic carrier-magnesium halide composite support. In certain embodiments, the amount of the polyvinyl polycarboxylate is 0.025g to 0.5g of polyvinyl polycarboxylate per gram of inorganic carrier-magnesium halide composite support. In certain embodiments, the amount of the polyvinyl polycarboxylate is 0.025g to 0.075g of polyvinyl polycarboxylate per gram of inorganic carrier-magnesium halide composite support.

[0046] In certain embodiments, in step 4), the inorganic carrier-magnesium halide composite carrier, polyethylene polycarboxylate and co-catalyst are mixed in a solvent at a temperature of 25°C to 70°C for 1 to 3 hours. In certain embodiments, in step 4), the inorganic carrier-magnesium halide composite carrier, polyethylene polycarboxylate and co-catalyst are mixed in a solvent at a temperature of 40°C to 60°C for 1 to 3 hours. In certain embodiments, in step 4), the inorganic carrier-magnesium halide composite carrier, polyethylene polycarboxylate and co-catalyst are mixed in a solvent at a temperature of 50°C for 1 to 3 hours.

[0047] In certain embodiments, the metallocene compound has a structure shown in Formula I,

[0048]

[0049] Wherein, R1 to R5 are each independently selected from H and C 1~6 In the alkyl group, M is a transition metal element, preferably a transition metal of Group 3, Group 4, Group 5, Group 6, lanthanide or osmium series of the periodic table, more preferably zirconium, titanium or hafnium.

[0050] In certain embodiments, R1 to R5 are each independently selected from H, methyl, ethyl, n-propyl, isopropyl, n-butyl, sec-butyl, isobutyl, tert-butyl, n-pentyl, and n-hexyl.

[0051] In certain embodiments, the metallocene compound is bis(n-butylcyclopentadienyl)zirconium dichloride.

[0052] In certain embodiments, the amount of the metallocene compound used is 10-50 mg per gram of the inorganic carrier-magnesium halide composite support, preferably 15-40 mg per gram of the inorganic carrier-magnesium halide composite support, and further preferably 20-30 mg per gram of the inorganic carrier-magnesium halide composite support, for example 25 mg.

[0053] In certain embodiments, the cocatalyst is alkylaluminoxane or alkylaluminum, and its usage is based on the ratio of transition metal atoms to aluminum atoms in the metallocene mixture, and the ratio of the number of transition metal atoms to aluminum atoms is 1:2 to 1200, preferably 1:10 to 300.

[0054] In certain embodiments, in step 5), the solid product separated in step 4) and the metallocene compound are mixed in a solvent at a temperature of 25°C to 70°C for 1 to 3 hours. In certain embodiments, in step 5), the solid product separated in step 4) and the metallocene compound are mixed in a solvent at a temperature of 40°C to 60°C for 1 to 3 hours. In certain embodiments, in step 5), the solid product separated in step 4) and the metallocene compound are mixed in a solvent at a temperature of 50°C for 1 to 3 hours.

[0055] In certain embodiments, the solvent is toluene, benzene, n-pentane, isopentane, hexane, heptane, octane or decane. In certain embodiments, the solvent is preferably n-hexane, n-heptane or toluene. In certain embodiments, the solvent is toluene. In certain embodiments, the water content of the solvent is 0.1 to 20 ppm. In certain embodiments, the water content of the solvent is 1 to 5 ppm.

[0056] In the present invention, the alcohol compound is composed of a straight-chain or branched fatty alkyl group and a hydroxyl group, the number of hydroxyl groups is preferably 1 or 2, and the number of carbon atoms is preferably 2 to 22, more preferably 2 to 11, and more preferably 2 to 8. In some embodiments, the alcohol mixture includes ethanol, n-propanol, isopropanol, n-butanol, neobutanol, isooctyl alcohol, 2-ethylbutanol, ethylene glycol, and the like.

[0057] In the present invention, the term "alkylaluminoxane" refers to open-chain or cyclic aluminoxane compounds, including methylaluminoxane (MAO), ethylaluminoxane, isobutylaluminoxane, etc., and corresponding modified compounds, such as modified methylaluminoxane, polymethylaluminoxane, etc.

[0058] In the present invention, the term "alkyl aluminum" refers to a large class of metallic aluminum organic compounds formed by direct combination of an alkyl group and aluminum, including trimethyl aluminum, triethyl aluminum, triisobutyl aluminum, trihexylaluminum and butyl aluminum.

[0059] In the present invention, the term "organic boron compound" refers to an organic compound containing a BC bond or a boron atom, including borane, hydrocarbon-substituted boranes and nitrogen-containing borides. Typical organic boron compounds include at least one of tris(pentafluorophenyl)boron (B(C6F5)3), trityltetrakis(pentafluorophenyl)borate, and dioctadecylmethyltertiaryaminetetrakis(pentafluorophenyl)borate.

[0060] In the present invention, the molecular structure formula of the term "polyvinyl polycarboxylate" is -[(CH2CH2)a-(CH2CHCOOR)b]n-, wherein n represents the molecular weight after polymerization, n is 1000-30000 g / mol, R is C 1~6 Alkyl, a≥1, b≥1, and a, b are integers. In some embodiments, the polyvinyl polycarboxylate is polyvinyl methyl acrylate, polyvinyl acrylic acid, polypropylene 2-methyl methacrylate, and the like.

[0061] In the present invention, the term "alkyl" refers to a saturated straight-chain or branched monovalent hydrocarbon group, preferably having 1 to 8 carbon atoms, more preferably 1 to 6, 1 to 4 or 1 to 3 carbon atoms. 1~8 Alkyl" or "C 1~6 "Alkyl" refers to an alkyl group having a specified number of carbon atoms, which is a straight chain or branched chain alkyl group, and which may include its subgroups, such as C 1~5 Alkyl, C 1~4 Alkyl, C 1~3 Alkyl, C 1~2 Alkyl, C 2~5 Alkyl, C 2~4 Alkyl, etc. Typical examples of "alkyl" include, but are not limited to, methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, sec-butyl, tert-butyl, n-pentyl, tert-pentyl, neopentyl, hexyl, heptyl, octyl, etc.

[0062] As used herein, the term "alkoxy" refers to an alkyl group as defined above attached to the parent molecular moiety through an oxygen atom. 1~8 "Alkoxy" refers to an alkoxy group having a specified number of carbon atoms, which may include its subgroups, such as C 1~6 Alkoxy, C 1~4 Alkoxy, C 1~3 Alkoxy, C 1~2 Alkoxy, C 2~5 Alkoxy, C 2~4 Alkoxy, etc. Typical examples of "alkoxy" include, but are not limited to, methoxy, ethoxy, n-propoxy, isopropoxy, n-butoxy, isobutoxy, tert-butoxy, sec-butoxy, n-pentoxy, n-hexyloxy, 1,2-dimethylbutoxy, and the like.

[0063] Beneficial technical effects of the present invention

[0064] The catalyst provided by the embodiment of the present invention has high catalytic ethylene polymerization activity and good copolymerization performance.

[0065] The catalyst provided in the embodiment of the present invention is used to catalyze ethylene polymerization to prepare a polymer non-stick kettle.

[0066] The catalyst provided in the embodiment of the present invention adopts an inorganic carrier-magnesium halide composite carrier, which can give the metallocene catalyst a better particle morphology, while increasing the surface area and pore volume of the carrier, thereby improving the loading effect of the active components.

[0067] The catalyst provided in the embodiment of the present invention introduces polyethylene polycarboxylate as a regulator, which can enable the carrier to load more metallocene compounds, reduce the amount of alkylaluminoxane used, make the catalyst have higher catalytic ethylene polymerization activity, and save production costs.

[0068] In the embodiment of the present invention, the activated carrier is activated by a one-step programmed temperature control method, and the dried inorganic carrier-magnesium halide composite carrier is quickly transferred to an activation furnace for activation, thereby reducing the process of cooling down and then heating up the carrier between the carrier drying and activation steps, saving costs while reducing the damage of the thermal history to the microscopic morphological structure of the carrier, and can better maintain the original morphological characteristics of the inorganic carrier, including microstructural characteristics such as the carrier pore structure, pore volume, and specific surface area. DETAILED DESCRIPTION

[0069] The substantive content of the present invention is further described below in conjunction with specific embodiments of the present invention. It should be understood that the following examples are only used to illustrate the present invention, but are not intended to limit the scope of protection of the present invention. In the following examples, if specific conditions are not specified, they are carried out according to conventional conditions or manufacturer recommendations. The raw materials used are not specified by the manufacturer, and are all conventional products that can be obtained commercially.

[0070] Although many materials and operating methods used in the following examples are well known in the art, the present invention is still described in as much detail as possible. It is clear to those skilled in the art that the materials and operating methods used in the following examples are well known in the art unless otherwise specified.

[0071] Some of the raw materials used in the embodiments of the present invention include:

[0072] 955 silica gel, specific surface area is 300m 2 / g, purchased from Grace, USA;

[0073] Alumina powder, chemical formula Al2O3, specific surface area 350m 2 / g, purchased from Beijing Inokai Technology Co., Ltd.;

[0074] Methylaluminoxane (MAO), 10 wt.%, purchased from Merck KGaA, Darmstadt, Germany;

[0075] Polyethylene polycarboxylate (molecular weight 3000 g / mol) with methyl acrylate content of 5 mol% was purchased from DuPont, USA;

[0076] Polyethylene polycarboxylate (molecular weight 3200 g / mol) with methyl acrylate content of 7 mol% was purchased from DuPont, USA;

[0077] Di(n-butylcyclopentadienyl)zirconium dichloride was purchased from Jiangsu Xinnoko Catalyst Co., Ltd.

[0078] Example 1

[0079] 1. Preparation of silica gel / MgCl2 composite carrier:

[0080] The preparation of silica gel / MgCl2 composite carrier was carried out under argon atmosphere. 1g of anhydrous magnesium chloride was dissolved in 5mL of ethanol at 70°C and stirred for 30min to obtain a magnesium chloride-ethanol alcoholate solution; then 4g of 955 silica gel was added, immersed at 70°C for 1h and then vacuum dried for 4h to obtain a SiO2 / MgCl2 composite carrier; the composite carrier was transferred to a tubular furnace for activation, the air flow was adjusted to make it fluidized, the temperature was first raised to 200°C, then raised to 450°C, kept constant for 4h, discharged after cooling, and sealed for storage for later use.

[0081] 2. Preparation of catalyst:

[0082] The catalyst was prepared under an argon atmosphere. 4 g of the activated composite carrier was dispersed in 40 mL of a toluene solution of MAO (10 wt%), 0.1 g of a polyethylene polycarboxylate (molecular weight 3000 g / mol) with a methyl acrylate content of 5 mol% was added, the mixture was stirred at room temperature for 0.5 h, then heated to 50° C. and stirred for 2 h, the solid was separated, then washed with toluene for 3 times, the obtained solid was redispersed in 40 mL of a toluene solution, 100 mg of di(n-butylcyclopentadienyl)zirconium dichloride was added, the solid was separated, the solid was washed with toluene for 3 times, and the catalyst was obtained after being fully dried for standby use.

[0083] 3.Polymerization process:

[0084] A 2L stainless steel polymerization kettle was replaced with high-purity nitrogen for no less than three times, and then 1.2L n-hexane was added into the kettle. After stirring, the temperature was raised to 90°C. After adding 50mg of catalyst, ethylene was injected until the system pressure reached 1.0MPa. After polymerization at constant temperature and pressure for 1h, the temperature was lowered, the material was discharged and dried to obtain an ethylene polymer.

[0085] Example 2

[0086] 1. Preparation of silica gel / MgCl2 composite carrier:

[0087] The preparation of silica gel / MgCl2 composite carrier was carried out under argon atmosphere. 1g of anhydrous magnesium chloride was dissolved in 5mL of ethanol at 70°C and stirred for 30min to obtain a magnesium chloride-ethanol alcoholate solution; then 4g of 955 silica gel was added, and the mixture was immersed at 70°C for 2h and then vacuum dried for 4h to obtain a SiO2 / MgCl2 composite carrier; the composite carrier was transferred to a tubular furnace for activation, and the air flow was adjusted to make it fluidized. The temperature was first raised to 200°C, then raised to 450°C, and kept constant for 4h. After cooling, the mixture was discharged and sealed for storage.

[0088] 2. Preparation of catalyst:

[0089] The catalyst was prepared under an argon atmosphere. 4 g of the activated composite carrier was dispersed in 40 mL of a toluene solution of MAO (10 wt%), 0.1 g of a polyethylene polycarboxylate (molecular weight 3000 g / mol) with a methyl acrylate content of 5 mol% was added, the mixture was stirred at room temperature for 0.5 h, then heated to 50° C. and stirred for 2 h, the solid was separated, then washed with toluene for 3 times, the obtained solid was redispersed in 40 mL of a toluene solution, 100 mg of di(n-butylcyclopentadienyl)zirconium dichloride was added, the solid was separated, the solid was washed with toluene for 3 times, and the catalyst was obtained after being fully dried for standby use.

[0090] 3.Polymerization process:

[0091] A 2L stainless steel polymerization kettle was replaced with high-purity nitrogen for no less than three times, and then 1.2L n-hexane was added into the kettle. After stirring, the temperature was raised to 90°C. After adding 50mg of catalyst, ethylene was injected until the system pressure reached 1.0MPa. After polymerization at constant temperature and pressure for 1h, the temperature was lowered, the material was discharged and dried to obtain an ethylene polymer.

[0092] Example 3

[0093] 1. Preparation of silica gel / MgCl2 composite carrier:

[0094] The preparation of silica gel / MgCl2 composite carrier was carried out under argon atmosphere. 1g of anhydrous magnesium chloride was dissolved in 5mL of ethanol at 70°C and stirred for 30min to obtain a magnesium chloride-ethanol alcoholate solution; then 4g of 955 silica gel was added, and the mixture was immersed at 70°C for 3h and then vacuum dried for 4h to obtain a SiO2 / MgCl2 composite carrier; the composite carrier was transferred to a tubular furnace for activation, and the air flow was adjusted to make it fluidized. The temperature was first raised to 200°C, then raised to 450°C, and kept constant for 4h. After cooling, the mixture was discharged and sealed for storage.

[0095] 2. Preparation of catalyst:

[0096] The catalyst was prepared under an argon atmosphere. 4 g of the activated composite carrier was dispersed in 40 mL of a toluene solution of MAO (10 wt%), 0.1 g of a polyethylene polycarboxylate (molecular weight 3000 g / mol) with a methyl acrylate content of 5 mol% was added, the mixture was stirred at room temperature for 0.5 h, then heated to 50° C. and stirred for 2 h, the solid was separated, then washed with toluene for 3 times, the obtained solid was redispersed in 40 mL of a toluene solution, 100 mg of di(n-butylcyclopentadienyl)zirconium dichloride was added, the solid was separated, the solid was washed with toluene for 3 times, and the catalyst was obtained after being fully dried for standby use.

[0097] 3.Polymerization process:

[0098] A 2L stainless steel polymerization kettle was replaced with high-purity nitrogen for no less than three times, and then 1.2L n-hexane was added into the kettle. After stirring, the temperature was raised to 90°C. After adding 50mg of catalyst, ethylene was injected until the system pressure reached 1.0MPa. After polymerization at constant temperature and pressure for 1h, the temperature was lowered, the material was discharged and dried to obtain an ethylene polymer.

[0099] Example 4

[0100] 1. Preparation of silica gel / MgCl2 composite carrier:

[0101] The preparation of silica gel / MgCl2 composite carrier was carried out under argon atmosphere. 1g of anhydrous magnesium chloride was dissolved in 5mL of ethanol at 70°C and stirred for 30min to obtain a magnesium chloride-ethanol alcoholate solution; then 4g of 955 silica gel was added, and the mixture was immersed at 70°C for 2h and then vacuum dried for 4h to obtain a SiO2 / MgCl2 composite carrier; the composite carrier was transferred to a tubular furnace for activation, and the air flow was adjusted to make it fluidized. The temperature was first raised to 200°C, then raised to 450°C, and kept constant for 4h. After cooling, the mixture was discharged and sealed for storage.

[0102] 2. Preparation of catalyst:

[0103] The catalyst was prepared under an argon atmosphere. 4 g of the activated composite carrier was dispersed in 40 mL of a toluene solution of MAO (10 wt%), 0.2 g of a polyethylene polycarboxylate (molecular weight 3000 g / mol) with a methyl acrylate content of 5 mol% was added, the mixture was stirred at room temperature for 0.5 h, then heated to 50° C. and stirred for 2 h, the solid was separated, then washed with toluene for 3 times, the solid was redispersed in 40 mL of a toluene solution, 100 mg of di(n-butylcyclopentadienyl)zirconium dichloride was added, the solid was separated, the solid was washed with toluene for 3 times, the catalyst was obtained after being fully dried and was ready for use.

[0104] 3.Polymerization process:

[0105] A 2L stainless steel polymerization kettle was replaced with high-purity nitrogen for no less than three times, and then 1.2L n-hexane was added into the kettle. After stirring, the temperature was raised to 90°C. After adding 50mg of catalyst, ethylene was injected until the system pressure reached 1.0MPa. After polymerization at constant temperature and pressure for 1h, the temperature was lowered, the material was discharged and dried to obtain an ethylene polymer.

[0106] Example 5

[0107] 1. Preparation of silica gel / MgCl2 composite carrier:

[0108] The preparation of silica gel / MgCl2 composite carrier was carried out under argon atmosphere. 1g of anhydrous magnesium chloride was dissolved in 5mL of ethanol at 70°C and stirred for 30min to obtain a magnesium chloride-ethanol alcoholate solution; then 4g of 955 silica gel was added, and the mixture was immersed at 70°C for 2h and then vacuum dried for 4h to obtain a SiO2 / MgCl2 composite carrier; the composite carrier was transferred to a tubular furnace for activation, and the air flow was adjusted to make it fluidized. The temperature was first raised to 200°C, then raised to 450°C, and kept constant for 4h. After cooling, the mixture was discharged and sealed for storage.

[0109] 2. Preparation of catalyst:

[0110] The catalyst was prepared under an argon atmosphere. 4 g of the activated composite carrier was dispersed in 40 mL of a toluene solution of MAO (10 wt%), 0.3 g of a polyethylene polycarboxylate (molecular weight 3000 g / mol) with a methyl acrylate content of 5 mol% was added, the mixture was stirred at room temperature for 0.5 h, then heated to 50° C. and stirred for 2 h, the solid was separated, then washed with toluene 3 times, the obtained solid was redispersed in 40 mL of toluene solution, 100 mg of di(n-butylcyclopentadienyl)zirconium dichloride was added, the solid was separated, the solid was washed with toluene 3 times, and the catalyst was obtained after being fully dried for standby use.

[0111] 3.Polymerization process:

[0112] A 2L stainless steel polymerization kettle was replaced with high-purity nitrogen for no less than three times, and then 1.2L n-hexane was added into the kettle. After stirring, the temperature was raised to 90°C. After adding 50mg of catalyst, ethylene was injected until the system pressure reached 1.0MPa. After polymerization at constant temperature and pressure for 1h, the temperature was lowered, the material was discharged and dried to obtain an ethylene polymer.

[0113] Example 6

[0114] 1. Preparation of silica gel / MgCl2 composite carrier:

[0115] The preparation of silica gel / MgCl2 composite carrier was carried out under argon atmosphere. 1g of anhydrous magnesium chloride was dissolved in 5mL of ethanol at 70°C and stirred for 30min to obtain a magnesium chloride-ethanol alcoholate solution; then 4g of 955 silica gel was added, and the mixture was immersed at 70°C for 2h and then vacuum dried for 4h to obtain a SiO2 / MgCl2 composite carrier; the composite carrier was transferred to a tubular furnace for activation, and the air flow was adjusted to make it fluidized. The temperature was first raised to 200°C, then raised to 450°C, and kept constant for 4h. After cooling, the mixture was discharged and sealed for storage.

[0116] 2. Preparation of catalyst:

[0117] The catalyst was prepared under an argon atmosphere. 4 g of the activated composite carrier was dispersed in 40 mL of a toluene solution of MAO (10 wt%), 0.1 g of a polyethylene polycarboxylate (molecular weight 3200 g / mol) with a methyl acrylate content of 7 mol% was added, the mixture was stirred at room temperature for 0.5 h, the temperature was raised to 50° C. and stirred for 2 h, the solid was separated, and then the solid was washed with toluene 3 times, the obtained solid was redispersed in 40 mL of toluene solution, 100 mg of di(n-butylcyclopentadienyl)zirconium dichloride was added, the solid was separated, the solid was washed with toluene 3 times, and the catalyst was obtained after being fully dried for standby use.

[0118] 3.Polymerization process:

[0119] A 2L stainless steel polymerization kettle was replaced with high-purity nitrogen for no less than three times, and then 1.2L n-hexane was added into the kettle. After stirring, the temperature was raised to 90°C. After adding 50mg of catalyst, ethylene was injected until the system pressure reached 1.0MPa. After polymerization at constant temperature and pressure for 1h, the temperature was lowered, the material was discharged and dried to obtain an ethylene polymer.

[0120] Example 7

[0121] 1. Preparation of silica gel / MgCl2 composite carrier:

[0122] The preparation of silica gel / MgCl2 composite carrier was carried out under argon atmosphere. 1g of anhydrous magnesium chloride was dissolved in 5mL of ethanol at 70°C and stirred for 30min to obtain a magnesium chloride-ethanol alcoholate solution; then 4g of 955 silica gel was added, and the mixture was immersed at 70°C for 2h and then vacuum dried for 4h to obtain a SiO2 / MgCl2 composite carrier; the composite carrier was transferred to a tubular furnace for activation, and the air flow was adjusted to make it fluidized. The temperature was first raised to 200°C, then raised to 450°C, and kept constant for 4h. After cooling, the mixture was discharged and sealed for storage.

[0123] 2. Preparation of catalyst:

[0124] The catalyst was prepared under an argon atmosphere. 4 g of the activated composite carrier was dispersed in 40 mL of a toluene solution of MAO (10 wt%), 0.2 g of a polyethylene polycarboxylate (molecular weight 3200 g / mol) with a methyl acrylate content of 7 mol% was added, the mixture was stirred at room temperature for 0.5 h, then heated to 50° C. and stirred for 2 h, the solid was separated, then washed with toluene for 3 times, the solid was redispersed in 40 mL of a toluene solution, 100 mg of di(n-butylcyclopentadienyl)zirconium dichloride was added, the solid was separated, the solid was washed with toluene for 3 times, the catalyst was obtained after being fully dried and was ready for use.

[0125] 3.Polymerization process:

[0126] A 2L stainless steel polymerization kettle was replaced with high-purity nitrogen for no less than three times, and then 1.2L n-hexane was added into the kettle. After stirring, the temperature was raised to 90°C. After adding 50mg of catalyst, ethylene was injected until the system pressure reached 1.0MPa. After polymerization at constant temperature and pressure for 1h, the temperature was lowered, the material was discharged and dried to obtain an ethylene polymer.

[0127] Example 8

[0128] 1. Preparation of silica gel / MgCl2 composite carrier:

[0129] The preparation of silica gel / MgCl2 composite carrier was carried out under argon atmosphere. 1g of anhydrous magnesium chloride was dissolved in 5mL of ethanol at 70°C and stirred for 30min to obtain a magnesium chloride-ethanol alcoholate solution; then 4g of 955 silica gel was added, and the mixture was immersed at 70°C for 2h and then vacuum dried for 4h to obtain a SiO2 / MgCl2 composite carrier; the composite carrier was transferred to a tubular furnace for activation, and the air flow was adjusted to make it fluidized. The temperature was first raised to 200°C, then raised to 450°C, and kept constant for 4h. After cooling, the mixture was discharged and sealed for storage.

[0130] 2. Preparation of catalyst:

[0131] The catalyst was prepared under an argon atmosphere. 4 g of the activated composite carrier was dispersed in 40 mL of a toluene solution of MAO (10 wt%), 0.3 g of a polyethylene polycarboxylate (molecular weight 3200 g / mol) with a methyl acrylate content of 7 mol% was added, the mixture was stirred at room temperature for 0.5 h, then heated to 50° C. and stirred for 2 h, the solid was separated, then washed with toluene for 3 times, the obtained solid was redispersed in 40 mL of a toluene solution, 100 mg of di(n-butylcyclopentadienyl)zirconium dichloride was added, the solid was separated, the solid was washed with toluene for 3 times, and the catalyst was obtained after being fully dried for standby use.

[0132] 3.Polymerization process:

[0133] A 2L stainless steel polymerization kettle was replaced with high-purity nitrogen for no less than three times, and then 1.2L n-hexane was added into the kettle. After stirring, the temperature was raised to 90°C. After adding 50mg of catalyst, ethylene was injected until the system pressure reached 1.0MPa. After polymerization at constant temperature and pressure for 1h, the temperature was lowered, the material was discharged and dried to obtain an ethylene polymer.

[0134] Example 9

[0135] 1. Preparation of silica gel / MgCl2 composite carrier:

[0136] The preparation of silica gel / MgCl2 composite carrier was carried out under argon atmosphere. 1g of anhydrous magnesium chloride was dissolved in 5mL of ethanol at 70°C and stirred for 30min to obtain a magnesium chloride-ethanol alcoholate solution; then 4g of 955 silica gel was added, and the mixture was immersed at 70°C for 2h and then vacuum dried for 4h to obtain a SiO2 / MgCl2 composite carrier; the composite carrier was transferred to a tubular furnace for activation, and the air flow was adjusted to make it fluidized. The temperature was first raised to 200°C, then raised to 450°C, and kept constant for 4h. After cooling, the mixture was discharged and sealed for storage.

[0137] 2. Preparation of catalyst:

[0138] The catalyst was prepared under an argon atmosphere. 4 g of the activated composite carrier was dispersed in 40 mL of a toluene solution of MAO (10 wt%), 0.3 g of a polyethylene polycarboxylate (molecular weight 3000 g / mol) with a methyl acrylate content of 5 mol% was added, the mixture was stirred at room temperature for 0.5 h, then heated to 50° C. and stirred for 2 h, the solid was separated, then washed with toluene 3 times, the obtained solid was redispersed in 40 mL of toluene solution, 100 mg of di(n-butylcyclopentadienyl)zirconium dichloride was added, the solid was separated, the solid was washed with toluene 3 times, and the catalyst was obtained after being fully dried for standby use.

[0139] 3.Polymerization process:

[0140] A 2L stainless steel polymerization kettle was replaced with high-purity nitrogen for no less than three times, and then 1.2L of n-hexane was added into the kettle. After stirring, the temperature was raised to 90°C. After adding 50mg of catalyst, 10mL of 1-hexene was injected, and ethylene was injected until the system pressure reached 1.0MPa. After polymerization at constant temperature and pressure for 1h, the temperature was lowered, the material was discharged and dried to obtain an ethylene polymer.

[0141] Example 10

[0142] 1. Preparation of silica gel / MgCl2 composite carrier:

[0143] The preparation of silica gel / MgCl2 composite carrier was carried out under argon atmosphere. 1g of anhydrous magnesium chloride was dissolved in 5mL of ethanol at 70°C and stirred for 30min to obtain a magnesium chloride-ethanol alcoholate solution; then 4g of 955 silica gel was added, and the mixture was immersed at 70°C for 2h and then vacuum dried for 4h to obtain a SiO2 / MgCl2 composite carrier; the composite carrier was transferred to a tubular furnace for activation, and the air flow was adjusted to make it fluidized. The temperature was first raised to 200°C, then raised to 450°C, and kept constant for 4h. After cooling, the mixture was discharged and sealed for storage.

[0144] 2. Preparation of catalyst:

[0145] The catalyst was prepared under an argon atmosphere. 4 g of the activated composite carrier was dispersed in 40 mL of a toluene solution of MAO (10 wt%), 0.2 g of a polyethylene polycarboxylate (molecular weight 3200 g / mol) with a methyl acrylate content of 7 mol% was added, the mixture was stirred at room temperature for 0.5 h, then heated to 50° C. and stirred for 2 h, the solid was separated, then washed with toluene for 3 times, the solid was redispersed in 40 mL of a toluene solution, 100 mg of di(n-butylcyclopentadienyl)zirconium dichloride was added, the solid was separated, the solid was washed with toluene for 3 times, the catalyst was obtained after being fully dried and was ready for use.

[0146] 3.Polymerization process:

[0147] A 2L stainless steel polymerization kettle was replaced with high-purity nitrogen for no less than three times, and then 1.2L of n-hexane was added into the kettle. After stirring, the temperature was raised to 90°C. After adding 50mg of catalyst, 10mL of 1-hexene was injected, and ethylene was injected until the system pressure reached 1.0MPa. After polymerization at constant temperature and pressure for 1h, the temperature was lowered, the material was discharged and dried to obtain an ethylene polymer.

[0148] Embodiment 11

[0149] 1. Preparation of alumina / MgCl2 composite carrier:

[0150] The preparation of the alumina / MgCl2 composite carrier was carried out under an argon atmosphere. 1 g of anhydrous magnesium chloride was dissolved in 5 mL of ethanol at 70 °C and stirred for 30 min to obtain a magnesium chloride-ethanol alcoholate solution; then 4 g of alumina powder (specific surface area 350 m 2 / g), immersed at 70°C for 2h and then vacuum dried for 4h to obtain an alumina / MgCl2 composite carrier; the composite carrier was transferred to a tubular furnace for activation, the airflow was adjusted to make it fluidized, the temperature was first raised to 200°C, then raised to 450°C, kept at a constant temperature for 4h, and then discharged after cooling, sealed and stored for later use.

[0151] 2. Preparation of catalyst:

[0152] The catalyst was prepared under an argon atmosphere. 4 g of the activated composite carrier was dispersed in 40 mL of a toluene solution of MAO (10 wt%), 0.1 g of a polyethylene polycarboxylate (molecular weight 3000 g / mol) with a methyl acrylate content of 5 mol% was added, the mixture was stirred at room temperature for 0.5 h, then heated to 50° C. and stirred for 2 h, the solid was separated, then washed with toluene for 3 times, the obtained solid was redispersed in 40 mL of a toluene solution, 100 mg of di(n-butylcyclopentadienyl)zirconium dichloride was added, the solid was separated, the solid was washed with toluene for 3 times, and the catalyst was obtained after being fully dried for standby use.

[0153] 3.Polymerization process:

[0154] A 2L stainless steel polymerization kettle was replaced with high-purity nitrogen for no less than three times, and then 1.2L n-hexane was added into the kettle. After stirring, the temperature was raised to 90°C. After adding 50mg of catalyst, ethylene was injected until the system pressure reached 1.0MPa. After polymerization at constant temperature and pressure for 1h, the temperature was lowered, the material was discharged and dried to obtain an ethylene polymer.

[0155] Example 12

[0156] 1. Preparation of alumina / MgCl2 composite carrier:

[0157] The preparation of the alumina / MgCl2 composite carrier was carried out under an argon atmosphere. 1 g of anhydrous magnesium chloride was dissolved in 5 mL of ethanol at 70 °C and stirred for 30 min to obtain a magnesium chloride-ethanol alcoholate solution; then 4 g of alumina powder (specific surface area 350 m 2 / g), immersed at 70°C for 2h and then vacuum dried for 4h to obtain an alumina / MgCl2 composite carrier; the composite carrier was transferred to a tubular furnace for activation, the airflow was adjusted to make it fluidized, the temperature was first raised to 200°C, then raised to 450°C, kept at a constant temperature for 4h, and then discharged after cooling, sealed and stored for later use.

[0158] 2. Preparation of catalyst:

[0159] The catalyst was prepared under an argon atmosphere. 4 g of the activated composite carrier was dispersed in 40 mL of a toluene solution of MAO (10 wt%), 0.2 g of a polyethylene polycarboxylate (molecular weight 3000 g / mol) with a methyl acrylate content of 5 mol% was added, the mixture was stirred at room temperature for 0.5 h, then heated to 50° C. and stirred for 2 h, the solid was separated, then washed with toluene for 3 times, the solid was redispersed in 40 mL of a toluene solution, 100 mg of di(n-butylcyclopentadienyl)zirconium dichloride was added, the solid was separated, the solid was washed with toluene for 3 times, the catalyst was obtained after being fully dried and was ready for use.

[0160] 3.Polymerization process:

[0161] A 2L stainless steel polymerization kettle was replaced with high-purity nitrogen for no less than three times, and then 1.2L n-hexane was added into the kettle. After stirring, the temperature was raised to 90°C. After adding 50mg of catalyst, ethylene was injected until the system pressure reached 1.0MPa. After polymerization at constant temperature and pressure for 1h, the temperature was lowered, the material was discharged and dried to obtain an ethylene polymer.

[0162] Embodiment 13

[0163] 1. Preparation of alumina / MgCl2 composite carrier:

[0164] The preparation of the alumina / MgCl2 composite carrier was carried out under an argon atmosphere. 1 g of anhydrous magnesium chloride was dissolved in 5 mL of ethanol at 70 °C and stirred for 30 min to obtain a magnesium chloride-ethanol alcoholate solution; then 4 g of alumina powder (specific surface area 350 m 2 / g), immersed at 70°C for 2h and then vacuum dried for 4h to obtain an alumina / MgCl2 composite carrier; the composite carrier was transferred to a tubular furnace for activation, the airflow was adjusted to make it fluidized, the temperature was first raised to 200°C, then raised to 450°C, kept at a constant temperature for 4h, and then discharged after cooling, sealed and stored for later use.

[0165] 2. Preparation of catalyst:

[0166] The catalyst was prepared under an argon atmosphere. 4 g of the activated composite carrier was dispersed in 40 mL of a toluene solution of MAO (10 wt%), 0.3 g of a polyethylene polycarboxylate (molecular weight 3000 g / mol) with a methyl acrylate content of 5 mol% was added, the mixture was stirred at room temperature for 0.5 h, then heated to 50° C. and stirred for 2 h, the solid was separated, then washed with toluene 3 times, the obtained solid was redispersed in 40 mL of toluene solution, 100 mg of di(n-butylcyclopentadienyl)zirconium dichloride was added, the solid was separated, the solid was washed with toluene 3 times, and the catalyst was obtained after being fully dried for standby use.

[0167] 3.Polymerization process:

[0168] A 2L stainless steel polymerization kettle was replaced with high-purity nitrogen for no less than three times, and then 1.2L n-hexane was added into the kettle. After stirring, the temperature was raised to 90°C. After adding 50mg of catalyst, ethylene was injected until the system pressure reached 1.0MPa. After polymerization at constant temperature and pressure for 1h, the temperature was lowered, the material was discharged and dried to obtain an ethylene polymer.

[0169] Embodiment 14

[0170] 1. Preparation of alumina / MgCl2 composite carrier:

[0171] The preparation of the alumina / MgCl2 composite carrier was carried out under an argon atmosphere. 1 g of anhydrous magnesium chloride was dissolved in 5 mL of ethanol at 70 °C and stirred for 30 min to obtain a magnesium chloride-ethanol alcoholate solution; then 4 g of alumina powder (specific surface area 350 m 2 / g), immersed at 70°C for 2h and then vacuum dried for 4h to obtain an alumina / MgCl2 composite carrier; the composite carrier was transferred to a tubular furnace for activation, the airflow was adjusted to make it fluidized, the temperature was first raised to 200°C, then raised to 450°C, kept at a constant temperature for 4h, and then discharged after cooling, sealed and stored for later use.

[0172] 2. Preparation of catalyst:

[0173] The catalyst was prepared under an argon atmosphere. 4 g of the activated composite carrier was dispersed in 40 mL of a toluene solution of MAO (10 wt%), 0.1 g of a polyethylene polycarboxylate (molecular weight 3200 g / mol) with a methyl acrylate content of 7 mol% was added, the mixture was stirred at room temperature for 0.5 h, the temperature was raised to 50° C. and stirred for 2 h, the solid was separated, and then the solid was washed with toluene 3 times, the obtained solid was redispersed in 40 mL of toluene solution, 100 mg of di(n-butylcyclopentadienyl)zirconium dichloride was added, the solid was separated, the solid was washed with toluene 3 times, and the catalyst was obtained after being fully dried for standby use.

[0174] 3.Polymerization process:

[0175] A 2L stainless steel polymerization kettle was replaced with high-purity nitrogen for no less than three times, and then 1.2L n-hexane was added into the kettle. After stirring, the temperature was raised to 90°C. After adding 50mg of catalyst, ethylene was injected until the system pressure reached 1.0MPa. After polymerization at constant temperature and pressure for 1h, the temperature was lowered, the material was discharged and dried to obtain an ethylene polymer.

[0176] Embodiment 15

[0177] 1. Preparation of alumina / MgCl2 composite carrier:

[0178] The preparation of the alumina / MgCl2 composite carrier was carried out under an argon atmosphere. 1 g of anhydrous magnesium chloride was dissolved in 5 mL of ethanol at 70 °C and stirred for 30 min to obtain a magnesium chloride-ethanol alcoholate solution; then 4 g of alumina powder (specific surface area 350 m 2 / g), immersed at 70°C for 2h and then vacuum dried for 4h to obtain an alumina / MgCl2 composite carrier; the composite carrier was transferred to a tubular furnace for activation, the airflow was adjusted to make it fluidized, the temperature was first raised to 200°C, then raised to 450°C, kept at a constant temperature for 4h, and then discharged after cooling, sealed and stored for later use.

[0179] 2. Preparation of catalyst:

[0180] The catalyst was prepared under an argon atmosphere. 4 g of the activated composite carrier was dispersed in 40 mL of a toluene solution of MAO (10 wt%), 0.2 g of a polyethylene polycarboxylate (molecular weight 3200 g / mol) with a methyl acrylate content of 7 mol% was added, the mixture was stirred at room temperature for 0.5 h, then heated to 50° C. and stirred for 2 h, the solid was separated, then washed with toluene for 3 times, the solid was redispersed in 40 mL of a toluene solution, 100 mg of di(n-butylcyclopentadienyl)zirconium dichloride was added, the solid was separated, the solid was washed with toluene for 3 times, the catalyst was obtained after being fully dried and was ready for use.

[0181] 3.Polymerization process:

[0182] A 2L stainless steel polymerization kettle was replaced with high-purity nitrogen for no less than three times, and then 1.2L n-hexane was added into the kettle. After stirring, the temperature was raised to 90°C. After adding 50mg of catalyst, ethylene was injected until the system pressure reached 1.0MPa. After polymerization at constant temperature and pressure for 1h, the temperature was lowered, the material was discharged and dried to obtain an ethylene polymer.

[0183] Example 16

[0184] 1. Preparation of alumina / MgCl2 composite carrier:

[0185] The preparation of the alumina / MgCl2 composite carrier was carried out under an argon atmosphere. 1 g of anhydrous magnesium chloride was dissolved in 5 mL of ethanol at 70 °C and stirred for 30 min to obtain a magnesium chloride-ethanol alcoholate solution; then 4 g of alumina powder (specific surface area 350 m 2 / g), immersed at 70°C for 2h and then vacuum dried for 4h to obtain an alumina / MgCl2 composite carrier; the composite carrier was transferred to a tubular furnace for activation, the airflow was adjusted to make it fluidized, the temperature was first raised to 200°C, then raised to 450°C, kept at a constant temperature for 4h, and then discharged after cooling, sealed and stored for later use.

[0186] 2. Preparation of catalyst:

[0187] The catalyst was prepared under an argon atmosphere. 4 g of the activated composite carrier was dispersed in 40 mL of a toluene solution of MAO (10 wt%), 0.3 g of a polyethylene polycarboxylate (molecular weight 3200 g / mol) with a methyl acrylate content of 7 mol% was added, the mixture was stirred at room temperature for 0.5 h, then heated to 50° C. and stirred for 2 h, the solid was separated, then washed with toluene for 3 times, the obtained solid was redispersed in 40 mL of a toluene solution, 100 mg of di(n-butylcyclopentadienyl)zirconium dichloride was added, the solid was separated, the solid was washed with toluene for 3 times, and the catalyst was obtained after being fully dried for standby use.

[0188] 3.Polymerization process:

[0189] A 2L stainless steel polymerization kettle was replaced with high-purity nitrogen for no less than three times, and then 1.2L n-hexane was added into the kettle. After stirring, the temperature was raised to 90°C. After adding 50mg of catalyst, ethylene was injected until the system pressure reached 1.0MPa. After polymerization at constant temperature and pressure for 1h, the temperature was lowered, the material was discharged and dried to obtain an ethylene polymer.

[0190] Embodiment 17

[0191] 1. Preparation of alumina / MgCl2 composite carrier:

[0192] The preparation of the alumina / MgCl2 composite carrier was carried out under an argon atmosphere. 1 g of anhydrous magnesium chloride was dissolved in 5 mL of ethanol at 70 °C and stirred for 30 min to obtain a magnesium chloride-ethanol alcoholate solution; then 4 g of alumina powder (specific surface area 350 m 2 / g), immersed at 70°C for 2h and then vacuum dried for 4h to obtain an alumina / MgCl2 composite carrier; the composite carrier was transferred to a tubular furnace for activation, the airflow was adjusted to make it fluidized, the temperature was first raised to 200°C, then raised to 450°C, kept at a constant temperature for 4h, and then discharged after cooling, sealed and stored for later use.

[0193] 2. Preparation of catalyst:

[0194] The catalyst was prepared under an argon atmosphere. 4 g of the activated composite carrier was dispersed in 40 mL of a toluene solution of MAO (10 wt%), 0.3 g of a polyethylene polycarboxylate (molecular weight 3000 g / mol) with a methyl acrylate content of 5 mol% was added, the mixture was stirred at room temperature for 0.5 h, then heated to 50° C. and stirred for 2 h, the solid was separated, then washed with toluene 3 times, the obtained solid was redispersed in 40 mL of toluene solution, 100 mg of di(n-butylcyclopentadienyl)zirconium dichloride was added, the solid was separated, the solid was washed with toluene 3 times, and the catalyst was obtained after being fully dried for standby use.

[0195] 3.Polymerization process:

[0196] A 2L stainless steel polymerization kettle was replaced with high-purity nitrogen for no less than three times, and then 1.2L of n-hexane was added into the kettle. After stirring, the temperature was raised to 90°C. After adding 50mg of catalyst, 10mL of 1-hexene was injected, and ethylene was injected until the system pressure reached 1.0MPa. After polymerization at constant temperature and pressure for 1h, the temperature was lowered, the material was discharged and dried to obtain an ethylene polymer.

[0197] Embodiment 18

[0198] 1. Preparation of alumina / MgCl2 composite carrier:

[0199] The preparation of the alumina / MgCl2 composite carrier was carried out under an argon atmosphere. 1 g of anhydrous magnesium chloride was dissolved in 5 mL of ethanol at 70 °C and stirred for 30 min to obtain a magnesium chloride-ethanol alcoholate solution; then 4 g of alumina powder (specific surface area 350 m 2 / g), immersed at 70°C for 2h and then vacuum dried for 4h to obtain an alumina / MgCl2 composite carrier; the composite carrier was transferred to a tubular furnace for activation, the airflow was adjusted to make it fluidized, the temperature was first raised to 200°C, then raised to 450°C, kept at a constant temperature for 4h, and then discharged after cooling, sealed and stored for later use.

[0200] 2. Preparation of catalyst:

[0201] The catalyst was prepared under an argon atmosphere. 4 g of the activated composite carrier was dispersed in 40 mL of a toluene solution of MAO (10 wt%), 0.2 g of a polyethylene polycarboxylate (molecular weight 3200 g / mol) with a methyl acrylate content of 7 mol% was added, the mixture was stirred at room temperature for 0.5 h, then heated to 50° C. and stirred for 2 h, the solid was separated, then washed with toluene for 3 times, the solid was redispersed in 40 mL of a toluene solution, 100 mg of di(n-butylcyclopentadienyl)zirconium dichloride was added, the solid was separated, the solid was washed with toluene for 3 times, the catalyst was obtained after being fully dried and was ready for use.

[0202] 3.Polymerization process:

[0203] A 2L stainless steel polymerization kettle was replaced with high-purity nitrogen for no less than three times, and then 1.2L of n-hexane was added into the kettle. After stirring, the temperature was raised to 90°C. After adding 50mg of catalyst, 10mL of 1-hexene was injected, and ethylene was injected until the system pressure reached 1.0MPa. After polymerization at constant temperature and pressure for 1h, the temperature was lowered, the material was discharged and dried to obtain an ethylene polymer.

[0204] Comparative Example 1

[0205] 1. Preparation of silica gel carrier:

[0206] The preparation of silica gel carrier was carried out under argon atmosphere. 4g 955 silica gel was dried for 4h to obtain SiO2 carrier; the dried SiO2 carrier was transferred to a tube furnace for activation, the air flow was adjusted to make it fluidized, the temperature was first raised to 200℃, then raised to 450℃, kept constant for 4h, and discharged after cooling, sealed and stored for later use.

[0207] 2. Preparation of catalyst:

[0208] The catalyst was prepared under an argon atmosphere. 4 g of activated SiO2 carrier was dispersed in 40 mL of MAO toluene solution (10 wt%), stirred at room temperature for 0.5 h, then heated to 50°C and stirred for 2 h, the solid was separated, then washed with toluene 3 times, the obtained solid was redispersed in 40 mL of toluene solution, 100 mg of di(n-butylcyclopentadienyl)zirconium dichloride was added, stirred at 50°C for 2 h, the solid was separated, washed with toluene 3 times, and the catalyst was obtained after being fully dried for standby use.

[0209] 3.Polymerization process:

[0210] A 2L stainless steel polymerization kettle was replaced with high-purity nitrogen for no less than three times, and then 1.2L of n-hexane was added into the kettle. After stirring, the temperature was raised to 90°C. After adding 50mg of catalyst, ethylene was injected until the system pressure reached 1.0MPa. After polymerization at constant temperature and pressure for 1h, the temperature was lowered, the material was discharged and dried to obtain an ethylene polymer.

[0211] Comparative Example 2

[0212] 1. Preparation of silica gel / MgCl2 composite carrier:

[0213] The preparation of silica gel / MgCl2 composite carrier was carried out under argon atmosphere. 1g of anhydrous magnesium chloride was dissolved in 5mL of ethanol at 70°C and stirred for 30min to obtain a magnesium chloride-ethanol alcoholate solution; then 4g of 955 silica gel was added, and the mixture was immersed at 70°C for 2h and then vacuum dried for 4h to obtain a SiO2 / MgCl2 composite carrier; the composite carrier was transferred to a tubular furnace for activation, and the air flow was adjusted to make it fluidized. The temperature was first raised to 200°C, then raised to 450°C, and kept constant for 4h. After cooling, the mixture was discharged and sealed for storage.

[0214] 2. Preparation of catalyst:

[0215] The catalyst was prepared under an argon atmosphere. 4 g of the activated composite carrier was dispersed in 40 mL of a toluene solution of MAO (10 wt%), stirred at room temperature for 0.5 h, then heated to 50° C. and stirred for 2 h, the solid was separated, then washed with toluene 3 times, the obtained solid was redispersed in 40 mL of toluene solution, 100 mg of di(n-butylcyclopentadienyl)zirconium dichloride was added, stirred at 50° C. for 2 h, the solid was separated, washed with toluene 3 times, and the catalyst was obtained after being fully dried for standby use.

[0216] 3.Polymerization process:

[0217] A 2L stainless steel polymerization kettle was replaced with high-purity nitrogen for no less than three times, and then 1.2L n-hexane was added into the kettle. After stirring, the temperature was raised to 90°C. After adding 50mg of catalyst, ethylene was injected until the system pressure reached 1.0MPa. After polymerization at constant temperature and pressure for 1h, the temperature was lowered, the material was discharged and dried to obtain an ethylene polymer.

[0218] Comparative Example 3

[0219] 1. Preparation of silica gel / MgCl2 composite carrier:

[0220] The preparation of silica gel / MgCl2 composite carrier was carried out under argon atmosphere. 1g of anhydrous magnesium chloride was dissolved in 5mL of ethanol at 70°C and stirred for 30min to obtain a magnesium chloride-ethanol alcoholate solution; then 4g of 955 silica gel was added, and the mixture was immersed at 70°C for 2h and then vacuum dried for 4h to obtain a SiO2 / MgCl2 composite carrier; the composite carrier was transferred to a tubular furnace for activation, and the air flow was adjusted to make it fluidized. The temperature was first raised to 200°C, then raised to 450°C, and kept constant for 4h. After cooling, the mixture was discharged and sealed for storage.

[0221] 2. Preparation of catalyst:

[0222] The catalyst was prepared under an argon atmosphere. 4 g of the activated composite carrier was dispersed in 40 mL of a toluene solution of MAO (10 wt%), stirred at room temperature for 0.5 h, then heated to 50° C. and stirred for 2 h, the solid was separated, then washed with toluene 3 times, the obtained solid was redispersed in 40 mL of toluene solution, 100 mg of di(n-butylcyclopentadienyl)zirconium dichloride was added, stirred at 50° C. for 2 h, the solid was separated, washed with toluene 3 times, and the catalyst was obtained after being fully dried for standby use.

[0223] 3.Polymerization process:

[0224] A 2L stainless steel polymerization kettle was replaced with high-purity nitrogen for no less than three times, and then 1.2L of n-hexane was added into the kettle. After stirring, the temperature was raised to 90°C. After adding 50mg of catalyst, 10mL of 1-hexene was injected, and ethylene was injected until the system pressure reached 1.0MPa. After polymerization at constant temperature and pressure for 1h, the temperature was lowered, the material was discharged and dried to obtain an ethylene polymer.

[0225] Comparative Example 4

[0226] 1. Preparation of alumina carrier:

[0227] The alumina carrier was prepared under argon atmosphere. 4 g of alumina powder (specific surface area 350 m 2 / g) and dried for 4 hours to obtain an alumina carrier; the dried alumina carrier was transferred to a tubular furnace for activation, the airflow was adjusted to make it fluidized, the temperature was first raised to 200°C, then raised to 450°C, and kept at a constant temperature for 4 hours, and then discharged after cooling, sealed and stored for later use.

[0228] 2. Preparation of catalyst:

[0229] The catalyst was prepared under an argon atmosphere. 4 g of the activated alumina carrier was dispersed in 40 mL of a toluene solution of MAO (10 wt%), stirred at room temperature for 0.5 h, then heated to 50° C. and stirred for 2 h, the solid was separated, then washed with toluene 3 times, the obtained solid was redispersed in 40 mL of toluene solution, 100 mg of di(n-butylcyclopentadienyl)zirconium dichloride was added, stirred at 50° C. for 2 h, the solid was separated, washed with toluene 3 times, and the catalyst was obtained after being fully dried for standby use.

[0230] 3.Polymerization process:

[0231] A 2L stainless steel polymerization kettle was replaced with high-purity nitrogen for no less than three times, and then 1.2L of n-hexane was added into the kettle. After stirring, the temperature was raised to 90°C. After adding 50mg of catalyst, ethylene was injected until the system pressure reached 1.0MPa. After polymerization at constant temperature and pressure for 1h, the temperature was lowered, the material was discharged and dried to obtain an ethylene polymer.

[0232] Comparative Example 5

[0233] 1. Preparation of alumina / MgCl2 composite carrier:

[0234] The preparation of the alumina / MgCl2 composite carrier was carried out under an argon atmosphere. 1 g of anhydrous magnesium chloride was dissolved in 5 mL of ethanol at 70 °C and stirred for 30 min to obtain a magnesium chloride-ethanol alcoholate solution; then 4 g of alumina powder (specific surface area 350 m 2 / g), immersed at 70°C for 2h and then vacuum dried for 4h to obtain an alumina / MgCl2 composite carrier; the composite carrier was transferred to a tubular furnace for activation, the airflow was adjusted to make it fluidized, the temperature was first raised to 200°C, then raised to 450°C, kept at a constant temperature for 4h, and then discharged after cooling, sealed and stored for later use.

[0235] 2. Preparation of catalyst:

[0236] The catalyst was prepared under an argon atmosphere. 4 g of the activated composite carrier was dispersed in 40 mL of a toluene solution of MAO (10 wt%), stirred at room temperature for 0.5 h, then heated to 50° C. and stirred for 2 h, the solid was separated, then washed with toluene 3 times, the obtained solid was redispersed in 40 mL of toluene solution, 100 mg of di(n-butylcyclopentadienyl)zirconium dichloride was added, stirred at 50° C. for 2 h, the solid was separated, washed with toluene 3 times, and the catalyst was obtained after being fully dried for standby use.

[0237] 3.Polymerization process:

[0238] A 2L stainless steel polymerization kettle was replaced with high-purity nitrogen for no less than three times, and then 1.2L n-hexane was added into the kettle. After stirring, the temperature was raised to 90°C. After adding 50mg of catalyst, ethylene was injected until the system pressure reached 1.0MPa. After polymerization at constant temperature and pressure for 1h, the temperature was lowered, the material was discharged and dried to obtain an ethylene polymer.

[0239] Comparative Example 6

[0240] 1. Preparation of alumina / MgCl2 composite carrier:

[0241] The preparation of the alumina / MgCl2 composite carrier was carried out under an argon atmosphere. 1 g of anhydrous magnesium chloride was dissolved in 5 mL of ethanol at 70 °C and stirred for 30 min to obtain a magnesium chloride-ethanol alcoholate solution; then 4 g of alumina powder (specific surface area 350 m 2 / g), immersed at 70°C for 2h and then vacuum dried for 4h to obtain an alumina / MgCl2 composite carrier; the composite carrier was transferred to a tubular furnace for activation, the airflow was adjusted to make it fluidized, the temperature was first raised to 200°C, then raised to 450°C, kept at a constant temperature for 4h, and then discharged after cooling, sealed and stored for later use.

[0242] 2. Preparation of catalyst:

[0243] The catalyst was prepared under an argon atmosphere. 4 g of the activated composite carrier was dispersed in 40 mL of a toluene solution of MAO (10 wt%), stirred at room temperature for 0.5 h, then heated to 50° C. and stirred for 2 h, the solid was separated, then washed with toluene 3 times, the obtained solid was redispersed in 40 mL of toluene solution, 100 mg of di(n-butylcyclopentadienyl)zirconium dichloride was added, stirred at 50° C. for 2 h, the solid was separated, washed with toluene 3 times, and the catalyst was obtained after being fully dried for standby use.

[0244] 3.Polymerization process:

[0245] A 2L stainless steel polymerization kettle was replaced with high-purity nitrogen for no less than three times, and then 1.2L of n-hexane was added into the kettle. After stirring, the temperature was raised to 90°C. After adding 50mg of catalyst, 10mL of 1-hexene was injected, and ethylene was added until the system pressure reached 1.0MPa. After polymerization at constant temperature and pressure for 1h, the temperature was lowered, the material was discharged and dried to obtain an ethylene polymer.

[0246] The polymerization activities of the catalysts prepared in the above-mentioned Examples 1 to 18 and Comparative Examples 1 to 6 of the present invention were calculated, and the results are listed in Table 1. The catalyst activity is expressed as the total weight of polyethylene obtained by the catalytic polymerization reaction per gram of catalyst in 1 hour, and the calculation formula is:

[0247] Polymerization activity (g PE / g Cat. / h) = total weight of polyethylene (g) ÷ weight of catalyst (g) ÷ polymerization reaction time (h).

[0248] In Table 1, A represents a polyethylene polycarboxylate (molecular weight 3000 g / mol) having a methyl acrylate content of 5 mol%, and B represents a polyethylene polycarboxylate (molecular weight 3200 g / mol) having a methyl acrylate content of 7 mol%.

[0249] Table 1 Polymerization activity of the catalysts prepared in the examples of the present invention

[0250]

[0251]

[0252]

[0253] The results showed that the time of immersion of silica gel in magnesium chloride-ethanol alcoholate solution, the molecular weight and dosage of polyethylene polycarboxylate would affect the loading efficiency of the catalyst and ultimately affect the polymerization activity.

[0254] It can be seen from Examples 1-3 that as the time for impregnating the support, such as silica gel, with the magnesium chloride-ethanol alcoholate solution increases, the polymerization activity of the catalyst increases. However, after more than 2 hours, the activity improvement is not obvious. Therefore, the time for impregnating the support with the magnesium chloride-ethanol alcoholate solution can be 1.8-3 hours, preferably 1.8-2.5 hours, and further preferably 1.8-2.2 hours.

[0255] Compared with single carrier silica gel or alumina, the use of silica gel / MgCl2 composite carrier or alumina / MgCl2 composite carrier can improve the polymerization activity of the catalyst, but the improvement is not large (Comparative Examples 1-3 and 4-6); while the use of silica gel / MgCl2 composite carrier or alumina / MgCl2 composite carrier combined with the addition of polyvinyl polycarboxylate can significantly improve the polymerization activity of the catalyst, and increasing the molecular weight and amount of polyvinyl polycarboxylate can improve the loading efficiency of the catalyst, thereby improving the polymerization activity of the catalyst (Examples 2, 4-8 and 11-16).

[0256] The polymerization activities of Examples 5, 7, 13 and 15 are much higher than those of Comparative Examples 1, 2, 4 and 5, indicating that the catalysts provided by the embodiments of the present invention have higher catalytic ethylene polymerization activities. It can be seen from Examples 9, 10, 17 and 18 that the catalysts provided by the embodiments of the present invention also have good copolymerization performance.

[0257] The inorganic carrier / magnesium halide composite carrier provided in the embodiment of the present invention can give the metallocene catalyst a better particle morphology, and the addition of polyethylene polycarboxylic acid ester improves the loading effect of the catalytic active components. The catalyst provided in the embodiment of the present invention reduces the amount of alkylaluminoxane used, and the catalyst saves production costs.

[0258] In the embodiment of the present invention, the activation carrier adopts a one-step method. The dried silica gel / MgCl2 composite carrier or alumina / MgCl2 composite carrier is transferred to an activation furnace for activation, which reduces the process of cooling down and then heating up between the carrier drying and activation steps, reduces the damage of the thermal history to the microscopic morphological structure of the carrier, and can better maintain the original morphological characteristics of the inorganic carrier, such as pore structure, pore volume, specific surface area and other structural characteristics.

[0259] Although the specific embodiments of the present invention have been described in detail, it will be understood by those skilled in the art that various modifications and substitutions may be made to those details based on all the teachings disclosed, and these changes are within the scope of protection of the present invention. The full scope of the present invention is given by the attached claims and any equivalents thereof.

Claims

1. A metallocene catalyst prepared by a method comprising the following steps: 1) providing a magnesium halide alcoholate solution; 2) adding the inorganic carrier to the magnesium halide alcoholate solution, impregnating, and obtaining an inorganic carrier-magnesium halide composite carrier; 3) Activating an inorganic carrier-magnesium halide composite carrier; 4) adding the activated inorganic carrier-magnesium halide composite carrier, polyethylene polycarboxylate, and co-catalyst to the solvent, mixing, and separating the solid product; 5) adding the solid product separated in step 4) and the metallocene compound into the solvent, mixing them evenly to obtain a metallocene catalyst.

2. The metallocene catalyst according to claim 1, wherein the magnesium halide alcoholate solution is prepared by a method comprising the following steps: 1-1) mixing a magnesium halide with an alcohol solution to obtain a mixture; 1-2) Stirring the obtained mixture at a temperature of 50° C. or higher and lower than the boiling point of the alcohol solution.

3. The metallocene catalyst according to claim 2, wherein the amount of the alcohol solution is 0.5 to 30 mL of alcohol solution per gram of magnesium halide, preferably 2 to 10 mL of alcohol solution per gram of magnesium halide, and further preferably 3 to 8 mL of alcohol solution per gram of magnesium halide, for example 5 mL of alcohol solution per gram of magnesium halide.

4. The metallocene catalyst according to claim 2 or 3, wherein the mixture is stirred for 20 to 480 min, preferably 20 to 90 min, and more preferably 30 to 90 min.

5. The metallocene catalyst according to claim 2 or 3, wherein the magnesium halide is selected from magnesium fluoride, chloride, bromide or iodide.

6. The metallocene catalyst of claim 5, wherein the magnesium halide is selected from magnesium dihalide, C 1~8 Alkyl magnesium halide, C 1~8 Alkoxymagnesium halides and any combination thereof.

7. The metallocene catalyst of claim 6, wherein the magnesium halide is selected from magnesium dichloride, magnesium dibromide, methylmagnesium chloride, methylmagnesium bromide, methoxymagnesium chloride, methoxymagnesium bromide, ethoxymagnesium chloride, ethoxymagnesium bromide, butoxymagnesium chloride, butoxymagnesium bromide and any combination thereof, preferably magnesium dichloride.

8. The metallocene catalyst according to claim 2 or 3, wherein the alcohol solution is an alcohol compound having 2 to 22 carbon atoms, preferably an alcohol compound having 2 to 11 carbon atoms, and more preferably an alcohol compound having 2 to 8 carbon atoms; Preferably, the alcohol solution is selected from ethanol, n-propanol, isopropanol, n-butanol, neobutanol, isooctyl alcohol, 2-ethylbutanol or ethylene glycol and any combination thereof, and more preferably ethanol.

9. The metallocene catalyst according to claim 8, wherein the alcohol solution is ethanol, and the mixture is stirred at a temperature of 50°C to 78°C (preferably 65°C to 78°C, such as 70°C).

10. The metallocene catalyst according to any one of claims 1 to 9, wherein the amount of the inorganic carrier is 1 to 10 g of inorganic carrier per gram of magnesium halide, preferably 2 to 6 g of inorganic carrier per gram of magnesium halide, further preferably 3 to 5 g of inorganic carrier per gram of magnesium halide, for example 4 g of inorganic carrier per gram of magnesium halide.

11. The metallocene catalyst according to any one of claims 1 to 10, wherein the impregnation temperature is -80°C to 90°C (preferably -20°C to 80°C, more preferably 60°C to 80°C, for example 70°C); the impregnation time is 0.5 to 6 hours, preferably 1 to 3 hours, further preferably 1.8 to 2.2 hours, for example 2 hours.

12. The metallocene catalyst according to any one of claims 1 to 11, wherein the inorganic carrier is silica gel, physicochemically modified silica gel, molecular sieve or alumina, preferably silica gel or alumina; Preferably, the average particle size of the inorganic carrier is 50 nm to 120 μm, preferably 0.5 to 5 μm; Preferably, the specific surface area of ​​the inorganic carrier is greater than or equal to 250 m 2 / g, preferably greater than or equal to 300m 2 / g, more preferably 300m 2 / g~600m 2 / g, for example 350m 2 / g, 400m 2 / g, 450m 2 / g、500m 2 / g.

13. The metallocene catalyst according to any one of claims 1 to 12, wherein step 2) further comprises drying the inorganic carrier / magnesium halide composite carrier, Preferably, the drying method is vacuum drying or temperature-controlled drying.

14. The metallocene catalyst according to claim 13, wherein the drying method is temperature-controlled drying. Preferably, the drying temperature is 30°C to 300°C, preferably 50°C to 150°C, and the drying time is 10 to 600 min, preferably 120 to 300 min, for example 240 min.

15. The metallocene catalyst according to any one of claims 1 to 14, wherein step 3) comprises: 3-1) placing the inorganic carrier-magnesium halide composite carrier in a fluidized state; 3-2) First raise the temperature to 200°C, then raise the temperature to 300°C to 800°C (preferably 400°C to 550°C, for example 400°C) and maintain a constant temperature.

16. The metallocene catalyst according to claim 15, wherein the constant temperature is maintained for 60 to 360 min, preferably for 120 to 300 min, for example 240 min.

17. The metallocene catalyst of any one of claims 1 to 16, wherein the cocatalyst is an alkylaluminoxane (e.g., methylaluminoxane, ethylaluminoxane, isobutylaluminoxane, modified methylaluminoxane, polymethylaluminoxane), an alkylaluminum (e.g., trimethylaluminum, triethylaluminum, triisobutylaluminum, trihexylaluminum, butylaluminum) or an organic boron compound (e.g., tris(pentafluorophenyl)boron (B(C6F5)3), trityltetrakis(pentafluorophenyl)borate, dioctadecylmethyltertiaryaminetetrakis(pentafluorophenyl)borate), Preferably, the cocatalyst is selected from methylaluminoxane, ethylaluminoxane, isobutylaluminoxane, triethylaluminum, triisobutylaluminum, preferably methylaluminoxane, triethylaluminum or triisobutylaluminum.

18. The metallocene catalyst according to any one of claims 1 to 17, wherein the general formula of the polyethylene polycarboxylate is -[(CH2CH2)a-(CH2CHCOOR)b]n-, wherein n represents the molecular weight after polymerization, n is 1000 to 30000 g / mol, wherein the molar content of the carboxylate is 0.5 to 16%, and R is C 1~6 Alkyl, such as methyl, ethyl, n-propyl, isopropyl, n-butyl, sec-butyl, isobutyl, tert-butyl, n-pentyl, n-hexyl, preferably methyl, a≥1, b≥1, and a, b are integers; Preferably, the polyvinyl polycarboxylate is a polyvinyl polycarboxylate having a methyl acrylate content of 5 to 7 mol% and a molecular weight of 3000 g / mol to 3200 g / mol. Preferably, the polyvinyl polycarboxylate is a polyvinyl polycarboxylate having a methyl acrylate content of 6 to 7 mol % and a molecular weight of 3000 g / mol to 3200 g / mol.

19. The metallocene catalyst according to any one of claims 1 to 18, wherein the amount of the polyvinyl polycarboxylate is 0.02 g to 2 g of polyvinyl polycarboxylate per gram of the inorganic carrier-magnesium halide composite carrier, preferably 0.025 g to 2 g of polyvinyl polycarboxylate per gram of the inorganic carrier-magnesium halide composite carrier, preferably 0.025 g to 1.0 g of polyvinyl polycarboxylate per gram of the inorganic carrier-magnesium halide composite carrier, preferably 0.025 g to 0.5 g of polyvinyl polycarboxylate per gram of the inorganic carrier-magnesium halide composite carrier, and preferably 0.025 g to 0.075 g of polyvinyl polycarboxylate per gram of the inorganic carrier-magnesium halide composite carrier.

20. The metallocene catalyst according to any one of claims 1 to 19, wherein in step 4), the inorganic carrier-magnesium halide composite carrier, polyethylene polycarboxylate and co-catalyst are mixed in a solvent at a temperature of 25°C to 70°C (preferably 40°C to 60°C, for example 50°C) for 1 to 3 hours.

21. The metallocene catalyst according to any one of claims 1 to 20, wherein the metallocene compound has a structure as shown in Formula I, in, R1 to R5 are each independently selected from H and C 1~6 In the alkyl group, M is a transition metal element, preferably a transition metal of Group 3, Group 4, Group 5, Group 6, lanthanide or osmium series of the periodic table, and more preferably zirconium, titanium or hafnium; Preferably, R1 to R5 are each independently selected from H, methyl, ethyl, n-propyl, isopropyl, n-butyl, sec-butyl, isobutyl, tert-butyl, n-pentyl, n-hexyl; Preferably, the metallocene compound is di(n-butylcyclopentadienyl)zirconium dichloride.

22. The metallocene catalyst according to any one of claims 1 to 21, wherein the amount of the metallocene compound is 10 to 50 mg per gram of the inorganic carrier-magnesium halide composite support, preferably 15 to 40 mg per gram of the inorganic carrier-magnesium halide composite support, and further preferably 20 to 30 mg per gram of the inorganic carrier-magnesium halide composite support, for example 25 mg. Preferably, the cocatalyst is alkylaluminoxane or alkylaluminum, and the amount thereof is calculated based on the ratio of transition metal atoms to aluminum atoms in the metallocene mixture, and the ratio of the number of transition metal atoms to aluminum atoms is 1:2 to 1200, preferably 1:10 to 300.

23. The metallocene catalyst according to any one of claims 1 to 22, wherein in step 5), the solid product separated in step 4) and the metallocene compound are mixed in a solvent at a temperature of 25°C to 70°C (preferably 40°C to 60°C, for example 50°C) for 1 to 3 hours.

24. The metallocene catalyst according to any one of claims 1 to 23, wherein the solvent is toluene, benzene, n-pentane, isopentane, hexane, heptane, octane or decane, preferably n-hexane, n-heptane or toluene, Preferably, the water content of the solvent is 0.1 to 20 ppm, preferably 1 to 5 ppm.

25. A method for preparing a metallocene catalyst, comprising the method according to any one of claims 1 to 24.

26. Use of the metallocene catalyst according to any one of claims 1 to 24 in catalytic synthesis of polyethylene.

Citation Information

Cited By

  • Metallocene catalyst precursor and preparation method thereof

    CN121471078A